Cognitive performance as a predictor of healthcare transition in sickle cell disease. (11th February 2021) - Saulsberry‐Abate, Anjelica C.; Partanen, Marita; Porter, Jerlym S.; Podila, Pradeep S. B.; Hodges, Jason R.; King, Allison A.; Wang, Winfred C.; Schreiber, Jane E.; Zhao, Xiwen; Kang, Guolian; Jacola, Lisa M.; Hankins, Jane S.
Summary: Neurocognitive deficits in sickle cell disease (SCD) may impair adult care engagement. We investigated the relationship between neurocognitive functioning and socio‐environmental factors with healthcare transition outcomes. Adolescents aged 15–18 years who had neurocognitive testing and completed a visit with an adult provider were included. Transition outcomes included transfer interval from paediatric to adult care and retention in adult care at 12 and 24 months. Eighty adolescents (59% male, 64% HbSS/HbSβ 0 ‐thalassaemia) were included. Mean age at adult care transfer was 18·0 (±0·3) years and transfer interval was 2·0 (±2·3) months. Higher IQ ( P  = 0·02; P FDR  = 0·05) and higher verbal comprehension ( P  = 0·008; P FDR  = 0·024) were associated with <2 and <6 month transfer intervals respectively. Better performance on measures of attention was associated with higher adult care retention at 12 and 24 months ( P  = 0·009; P FDR  = 0·05 and P  = 0·04; P FDR  = 0·12 respectively). Transfer intervals <6 months were associated with smaller households ( P  = 0·02; P FDR  = 0·06) and households with fewer children ( P  = 0·02; P FDR  = 0·06). Having a working parent was associated with less retention in adult care at 12 and 24 months ( P  = 0·01; P  = 0·02 respectively). Lower IQ, verbal comprehension, attention difficulties and environmental factors may negatively impact transition outcomes. Neurocognitive function should be considered in transition planning for youth with SCD.